2014
DOI: 10.5012/bkcs.2014.35.8.2481
|View full text |Cite
|
Sign up to set email alerts
|

Thieny/Furanyl-hydroxyphenylpropenones as Inhibitors of LPS-induced ROS and NO Production in RAW 264.7 Macrophages, and Their Structure-Activity Relationship Study

Abstract: Twelve thienyl/furanyl-hydroxyphenylpropenones were systematically designed and synthesized, and evaluated for their inhibitory effect on LPS-induced ROS and NO production in RAW 264.7 macrophages. Compound 11 displayed the most significant inhibitory activity of LPS-induced ROS and NO production in RAW 264.7 macrophages. Structure-activity relationship study indicated that para-hydroxyphenyl moiety plays an important role for inhibitory activities on both LPS-induced ROS and NO production as well as 3-thienyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Studies involving tetra substituted thiophene revealed good anti‐fungal and antibacterial properties and potent anti‐inflammatory properties of the thiophenes . Chalcone derivatives having thiophenyl, furanyl and/or hydroxyphenyl moiety (Figure (b)) illustrating the importance of hydroxyphenyl and thiophenyl moiety for inhibiting the production of ROS stimulated by LPS in RAW 264.7 macrophages was reported by our previous research group . 1‐Indanone and their derivatives have been extensively studied recently and have shown very good biological activity as anti‐inflammatory, anti‐cancer, antiviral, and antibacterial .…”
Section: Introductionmentioning
confidence: 99%
“…Studies involving tetra substituted thiophene revealed good anti‐fungal and antibacterial properties and potent anti‐inflammatory properties of the thiophenes . Chalcone derivatives having thiophenyl, furanyl and/or hydroxyphenyl moiety (Figure (b)) illustrating the importance of hydroxyphenyl and thiophenyl moiety for inhibiting the production of ROS stimulated by LPS in RAW 264.7 macrophages was reported by our previous research group . 1‐Indanone and their derivatives have been extensively studied recently and have shown very good biological activity as anti‐inflammatory, anti‐cancer, antiviral, and antibacterial .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some chalcone derivatives showed inhibitory effect on COX/5‐LOX and MCP‐1 expression in macrophages via inhibition of ROS and Akt signaling . Previously, our research group also reported synthesis and inhibitory activity of fluorophenyl and heterocyclic rings containing chalcone derivatives against LPS‐stimulated ROS production in RAW 264.7 macrophages (Figure (b)) . In a recent study, we reported synthesis of halogenated 2‐benzylidene‐1‐indanone derivatives (Figure (c)) as inhibitor of LPS‐stimulated ROS production via modulation of NADPH (Nicotinamide adenine dinucleotide phosphate) oxidase .…”
Section: Introductionmentioning
confidence: 77%
“…RAW 264.7 murine macrophages were purchased from the Korean cell line bank (Seoul, Korea) and routinely cultured in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% (vol/vol) fetal bovine serum (FBS) and 1% (vol/vol) penicillin‐streptomycin at an incubator with humidified atmosphere of 95% oxygen and 5% CO 2 …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these two compounds were not included for the continuing studies. In addition, we have previously shown that para -hydroxyphenyl moiety exhibits the most effective structure activity for anti-inflammatory responses, including suppression of nitric oxide (NO) and ROS production ( Kadayat et al ., 2014 ). Thus, among the compounds prepared for this study, we decided to focus on TI-I-175 for continuing study.…”
Section: Resultsmentioning
confidence: 99%
“…Excessive production of reactive oxygen species (ROS) is considered as a critical event contributing to inflict diverse pathophysiological events ( Apel and Hirt, 2004 ), although normal range of ROS is required for appropriate physiological processes as well. In particular, ROS is exceedingly produced in response to inflammatory stimuli ( Kadayat et al ., 2014 ) and considered as a critical mediator for inflammatory responses. Therefore, pharmacological modulation of excessive ROS production might be a promising strategy for the management of pathophysiological states associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%